Controlling Hox gene expression and activity to build the vertebrate axial skeleton - Casaca, Ana (2016)
It has long been known that Hox genes are central players in patterning the vertebrate axial skeleton. Extensive genetic studies in the mouse have revealed that the combinatorial activity of Hox genes along the anterior-posterior body axis specifies different vertebral identities. In addition, Hox genes were instrumental for the evolutionary diversification of the vertebrate body plan. In this review, we focus on fundamental questions regarding the intricate mechanisms controlling Hox gene activity. In particular, we discuss the functional relevance of the precise timing of Hox gene activation in the embryo. Moreover, we provide insight into the epigenetic regulatory mechanisms that are likely to control this process and are responsible for the maintenance of spatially restricted Hox expression domains throughout embryonic development. We also analyze how specific features of each Hox protein may contribute to the functional diversity of Hox family. Altogether, the work reviewed here further supports the notion that the Hox program is far more complex than initially assumed. Exciting new findings will surely emerge in the years ahead.